Translating Prohibition in Arabic Poetic Lines into English - Omar, Nida S. (Onomázein, 2020)
This study investigates the indirect meanings of prohibitive linguistic acts used in Arabic poetic lines. Prohibition has been an interest of Arab and English researchers. Arab researchers have focused on the indirect meanings of prohibition in the Quran without paying attention to its existence in poetic lines. When Arabic prohibitive poetic lines are translated into English, issues arise because of linguistic and, sometimes, cultural notions between two different languages. In this study, three research questions must be answered. (1) What are the indirect meanings of prohibitive poetic lines at the level of ideational meaning? (2) What are the types of the transitivity processes of prohibitive poetic lines in Arabic and English? (3) Which type of translation method is used in translating Arabic prohibitive poetic lines into English? On this ground, the study is based on Speech Act Theory by Searle (1976) to show how the language of the speech is organised to convey the meaning of the speaker to the hearer. Systemic Functional Linguistics by Halliday (1994) is also adopted to show how ideational function through prohibitive acts is communicated. Nida’s model for translation is also adopted to show methods in translating Arabic prohibitive poetic lines into English. The study has contended that direct and indirect meanings occurred within the scope of Searle’s classification. The process of prohibitive speech acts was subjected sometimes to change when translated into English. The present study has also exposed how the indirect meaning of Arabic prohibitive poetic lines is generally conveyed by formal translation and, sometimes, by dynamic translation and by both.